The taxonomic status of two geophytic Euphorbia species (Euphorbiaceae) from Maharashtra, India - Mane, Rohit N.; Nerlekar, Ashish N.; Lapalikar, Sairandhri A.; Kambale, Sharad S.; Yadav, Shrirang R. (Phytotaxa, 2017)
In the present communication, we resurrect E. khandallensis and synonymize E. panchganiensis under it owing to the overlap of distinguishing characters, as inferred from literature and first hand observations. We further provide an amended description of E. khandallensis along with critical notes on its taxonomy and distribution.